2023
DOI: 10.1093/nar/gkad124
|View full text |Cite
|
Sign up to set email alerts
|

Goldilocks and RNA: where Mg2+ concentration is just right

Abstract: Magnesium, the most abundant divalent cation in cells, catalyzes RNA cleavage but also promotes RNA folding. Because folding can protect RNA from cleavage, we predicted a ‘Goldilocks landscape’, with local maximum in RNA lifetime at Mg2+ concentrations required for folding. Here, we use simulation and experiment to discover an innate and sophisticated mechanism of control of RNA lifetime. By simulation we characterized RNA Goldilocks landscapes and their dependence on cleavage and folding parameters. Experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…While Mg 2+ is only found at concentrations of 10–30 mM in intracellular environments, most of the Mg 2+ tends to be bound to ribosomes, polynucleotides, and ATP . Still, RNA molecules are sensitive to the Mg 2+ concentration, where an optimal Mg 2+ concentration leads to a maximum lifetime of an RNA molecule . To analyze the rate at which Mg 2+ binds during our McMD simulations, we analyzed the reweighted structural ensemble and found that on average 14.65 Mg 2+ and 58.77 K + ions were bound simultaneously (i.e., within 5 Å) to the RNA, with the Mg 2+ binding density shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Mg 2+ is only found at concentrations of 10–30 mM in intracellular environments, most of the Mg 2+ tends to be bound to ribosomes, polynucleotides, and ATP . Still, RNA molecules are sensitive to the Mg 2+ concentration, where an optimal Mg 2+ concentration leads to a maximum lifetime of an RNA molecule . To analyze the rate at which Mg 2+ binds during our McMD simulations, we analyzed the reweighted structural ensemble and found that on average 14.65 Mg 2+ and 58.77 K + ions were bound simultaneously (i.e., within 5 Å) to the RNA, with the Mg 2+ binding density shown in Figure S8.…”
Section: Resultsmentioning
confidence: 99%
“… 44 Still, RNA molecules are sensitive to the Mg 2+ concentration, where an optimal Mg 2+ concentration leads to a maximum lifetime of an RNA molecule. 45 To analyze the rate at which Mg 2+ binds during our McMD simulations, we analyzed the reweighted structural ensemble and found that on average 14.65 Mg 2+ and 58.77 K + ions were bound simultaneously (i.e., within 5 Å) to the RNA, with the Mg 2+ binding density shown in Figure S8 . During the preparation of the system, 15 Mg and 106 K ions were added to the bulk solvent (randomly), suggesting that RNA is much more likely to bind to Mg 2+ than to bind to K + , and even higher concentrations of Mg 2+ might also be acceptable.…”
Section: Resultsmentioning
confidence: 99%
“…S6 ), which is roughly consistent with previous estimates of ∼1% RNA degradation after 72 hours in 1 M K + and 5 mM Mg 2+ at pH 9.5 ( 36 ). The relatively low concentration of divalent cations may compensate for the high pH in lake water to keep the hydrolysis rate low ( 37 ). However, we also observed that fewer primers had been extended by at least three nucleotides after 72 hours in lake water, relative to standard laboratory conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In another investigation, we tested the effects of salts containing multivalent ions, such as magnesium ions [ 23 ]. It has previously been reported that multivalent ions (such as magnesium) can have a significant effect on nucleic acid structure (folding) [ 24 , 25 ]. For this reason, MgSO 4 and MgCl 2 were added to the mobile phase in small amounts (2 and 10 mM) as a higher concentration of Mg 2+ ions is known to impact negatively the structure of nucleic acids as reported elsewhere [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that multivalent ions (such as magnesium) can have a significant effect on nucleic acid structure (folding) [ 24 , 25 ]. For this reason, MgSO 4 and MgCl 2 were added to the mobile phase in small amounts (2 and 10 mM) as a higher concentration of Mg 2+ ions is known to impact negatively the structure of nucleic acids as reported elsewhere [ 24 , 25 ]. The corresponding chromatograms are shown in Figure 2 and Figure S3 .…”
Section: Resultsmentioning
confidence: 99%